2010
DOI: 10.1021/es9039488
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Mercury Contamination Sources in Sediments Using Mercury Isotope Compositions

Abstract: Mercury (Hg) isotope ratios were determined in two sediment cores collected from two adjacent reservoirs in Guizhou, China, including Hongfeng Reservoir and Baihua Reservoir. Hg isotope compositions were also analyzed in a soil sample collected from the catchment of Hongfeng Reservoir and three cinnabar samples collected from the Wanshan Hg mine. Baihua Reservoir was contaminated with runoff from Guizhou Organic Chemical Plant (GOCP) when metallic Hg was used as a catalyst to produce acetic acid. Hongfeng Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
101
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 36 publications
8
101
0
1
Order By: Relevance
“…Sediments of the Baihua Reservoir, for example, received Hg pollution from the Guizhou Organic Chemical Plant and contain high levels of Hg (0.26-39 mg kg À1 ) [122]. Several studies have been performed that focus on the high potential for Hg methylation [122,123].…”
Section: Mercury In Heavily Contaminated Sitesmentioning
confidence: 99%
“…Sediments of the Baihua Reservoir, for example, received Hg pollution from the Guizhou Organic Chemical Plant and contain high levels of Hg (0.26-39 mg kg À1 ) [122]. Several studies have been performed that focus on the high potential for Hg methylation [122,123].…”
Section: Mercury In Heavily Contaminated Sitesmentioning
confidence: 99%
“…As a result, the initial studies of Hg isotopes suggest that their analysis within samples from sedimentary deposits, including those within riverine environments, may be used to assess both Hg sources and loading histories [105,193,232,[236][237][238]. Sonke et al [193], for example, found that within the Lot River basin, France metal refining resulted in slag residues that exhibited heavier Hg isotopic values, and both mass-dependent and mass-independent Hg isotopic signatures of contaminated sediments were significantly different (heavier) than that of the local background materials.…”
Section: Mercury Isotopesmentioning
confidence: 99%
“…Fractionation of Hg has been detected in a large variety of environmental compartments, e.g. hydrothermal Hg-bearing ores [8][9][10], coals [11,12], soil/sediments [7,[13][14][15], atmospheric Hg [16] and biological tissues [17]. Above cited studies have unequivocally demonstrated that variations in the Hg isotopic signature could be used in the future as tracers to distinguish between Hg sources and important chemical transformation processes in the environment.…”
mentioning
confidence: 99%
“…This model demonstrated that Hg MIF is a common phenomenon at the global scale and photo-reduction of aqueous Hg is the main MIF inducing process results in negative atmospheric ∆ 199 Hg. Hg for all surface soils (this study), coal samples from Guiyang [19], Hg ore and Hg waste samples collected from WSMM [14,28]. The isotope data in QZPP (n =3) are already published in ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation